已知因果信号[img=31x25]1803110566b7b11.png[/img]满足方程:[img=229x27]180311056efb4c8.png[/img],则利用拉氏变换可求得[img=31x25]180311057819b5c.png[/img]的表达式为( )。
未知类型:{'options': ['', '', '', ''], 'type': 102}
未知类型:{'options': ['', '', '', ''], 'type': 102}
举一反三
- 已知[img=31x25]18034a5f85455d7.png[/img]的拉氏变换为[img=124x43]18034a5f8dda3eb.png[/img], 求[img=31x25]18034a5f85455d7.png[/img]的Z变换。() 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 已知[img=31x25]18035f6a8307aa3.png[/img]的拉氏变换为[img=108x43]18035f6a8b356f7.png[/img], 求[img=31x25]18035f6a8307aa3.png[/img]的Z变换( ) 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 已知[img=31x25]1802fc8ea498ff4.png[/img]的拉氏变换为[img=108x43]1802fc8ead0626b.png[/img], 求[img=31x25]1802fc8ea498ff4.png[/img]的Z变换( ) 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 已知[img=31x25]1802fca0c54e48e.png[/img]的拉氏变换为[img=124x43]1802fca0ce73829.png[/img], 求[img=31x25]1802fca0c54e48e.png[/img]的Z变换。() 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 已知因果信号的拉普拉斯变换为[img=119x49]18031117dc28b88.png[/img],其原函数[img=31x25]18031117e443163.png[/img]为( )。 未知类型:{'options': ['', '', '', ''], 'type': 102}